2019
DOI: 10.15287/afr.2018.1163
|View full text |Cite
|
Sign up to set email alerts
|

Mapping forest aboveground biomass with a simulated ICESat-2 vegetation canopy product and Landsat data

Abstract: Mapping forest aboveground biomass with a simulated ICESat-2 vegetation canopy product and Landsat data. Ann. For. Res. 62(1): _-_.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…Using an ICESat-2 track over vegetation in Finland, the authors reported a horizontal accuracy of 5 m and vertical RMSEs of 0.85 m and 3.2 m for terrain and canopy heights, when comparing with spatially coincident airborne lidar data. Using ICESat-2-like data, synergies between ICESat-2 and Landsat are also well-noted [13,16,17] and given the near-global coverage of ICESat-2 over a nominal mission period of 3 years and spatially continuous Landsat imagery, opportunities for achieving wall-to-wall global coverage of vegetation parameters are encouraging.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…Using an ICESat-2 track over vegetation in Finland, the authors reported a horizontal accuracy of 5 m and vertical RMSEs of 0.85 m and 3.2 m for terrain and canopy heights, when comparing with spatially coincident airborne lidar data. Using ICESat-2-like data, synergies between ICESat-2 and Landsat are also well-noted [13,16,17] and given the near-global coverage of ICESat-2 over a nominal mission period of 3 years and spatially continuous Landsat imagery, opportunities for achieving wall-to-wall global coverage of vegetation parameters are encouraging.…”
Section: Introductionmentioning
confidence: 90%
“…This study utilized available airborne lidar-derived AGB estimates for SHNF previously used to model AGB from simulated ICESat-2 data [16,17], and methods for upscaling were implemented to cover the extent of the ICESat-2 transect. AGB for SHNF was estimated from airborne lidar and ground inventory data [14].…”
Section: Reference Aboveground Biomass (Agb) Mapmentioning
confidence: 99%
See 2 more Smart Citations
“…The aims of the ICESat-2 mission include to continue estimation of ice sheet elevation and sea ice freeboard to determine their changes (Markus et al, 2017). Besides, the detection of ground under dense canopy (Herzfeld et al, 2014), generating wall-towall AGB maps (Narine et al, 2019), estimating vegetation cover and biomass in a dry land ecosystem (Glenn et al, 2016) have been done based on the simulated data. It should be mentioned that the real data of the satellite have not been yet released.…”
Section: Adm-aeolus Satellitementioning
confidence: 99%